How to Effectively Serve Your Department by Being an Influential Leader - Shelley Rouser; Charlisa Edelin; Renee Marine (Academic Chairpersons Conference Proceedings, 2023)
For this workshop, we will invite Chairs to critically think about their role as a servant leader and how to pull six levers of influence to drive change. We will open the discussion with research and knowledge about the different types of leadership and concentrate on why influence is essential. Following the discussion, we will collaborate with Chairs in a consultative model on some influential servant leadership successes and challenges in a working session focused on generating practical next steps and workable solutions to the problems being faced.
Keywords: Servant leader; influential leader; academic leadership; diversity; department culture; change management